Factors Influencing the Purchase Intention of Basmati Rice in Chittoor District of Andhra Pradesh - Priyanka,; Aparna,; Prabhavathi,; Lavanyakumari, (Indian Journal of Extension Education, 2018)
Basmati rice is unique among other aromatic long grain rice varieties. Agro-climatic conditions of the specific geographical area, as well as method of harvesting, processing and aging, attribute these characteristic features to basmati rice. This paper made a humble attempt to understand the factors influencing the purchase intention of basmati rice in Chittoor district of Andhra Pradesh. Major retailers in the district were identified and five retailers were randomly chosen for the study. Thirty consumers visiting each retail shop were identified and randomly selected; the total sample size is 150. The collected data was analysed by using Likert scale and factor analysis. Seasoning factor was the most considered factor for purchase the basmati rice.
Keywords: Basmati rice; chittoor district; consumers’ preferences